Sustainable hospital for urban residents - Mohd. Din, Shamzani Affendy; Nik Yahya, Nik Nurul Hidayah; Othman, Rashidi (Universiti Teknologi Malaysia, 2015)
Malaysia is one of the sustainable countries in the world as it ranked at 51st over 178 countries in Environmental Performance Index (EPI). However, Malaysia as an upper-middle-income country set strong forces in Gross Domestic Production from 2009 until 2014 at 16.18 per cent (%) inclination. The urbanisation activities exposing the urban residents to the concentration of fine and ultrafine particulates matter (PM) include the urban area hospital occupants. The main aim of this research is to investigate the adverse health effects towards the patients in hospital specifically, Kuala Lumpur in general. Significantly, the outcome assist in particulate matter impact control in expenditure by general government and promotes the sustainable hospital ambient towards its occupants. The case study for this pilot study is Kuala Lumpur Hospital (HKL). The approaches used are literature review and data collections. The findings identified the motor vehicles as the main sources of Particulates Matter in Kuala Lumpur urban area. As the sources increases, the PM concentration also increases. Simultaneously, the number of patients facing respiratory related diseases also increased. Contradict to previous researchers’ theory, Malaysian results shows that as the number of unhealthy days increase in the year 2012, yet the morbidity case reported decreases. This is for the general government had spent at an increment of 7.46% in the year 2011 during the fall of unhealthy days at 11.76 % in 2011. This shows that the general government spend effectively to mitigate the repeat cases of respiratory patients facing by high risk communities. In conclusion, the sustainable development can be achieved as the economy is being blend well with the environment.